IITA receives innovation partnership award from Nestle - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
The Nestle Research Awards 2011 under the category "The innovation Partnership award was presented to International Institute of Tropical agriculture (IITA) in recognition of innovation of "Bio fortified yellow cassava and maize - increase bio availability of iron and Zinc.